Book Review: Petronel Zahariuc, Adrian-Bogdan Ceobanu (eds.), “160 de ani de la Unirea Principatelor: oameni, fapte şi idei din domnia lui Alexandru Ioan Cuza”, Iaşi, Editura Universităţii “Alexandru Ioan Cuza” din Iaşi, 2020), 666 p. - VARGA, Antonia-Annamaria (Studia Universitatis Babeș-Bolyai Historia, 2021)
The latter half of the 19th century brought forth a new dimension with regards to the further development of the Danubian Principalities. Even though foreign historiography tends to gravitate in its analyses towards the reign of King Charles the 1st, the beginning of the “modern Romanian state” is placed at an earlier date. With the year 1859 comes the unification of the two separate states into one nuclear entity under the rule of prince Alexandru Ioan Cuza (1859-1866). An iconic moment, with a plethora of ramifications and effects, both internal and external, the union truly marked the beginning of a new era. The historiography of his reign is a vast, but not an exhaustive one. The findings of new sources in the archives, the rapid development of technologies and methodologies applied to this area of study, or simply new interpretations of arguments already formulated, are of help in expanding not only the quantity, but also the quality of historical writing. The volume "160 de ani de la Unirea Principatelor: oamenii, fapte şi idei din domnia lui Alexandru Ioan Cuza" can be placed in such coordinates. Being the written form of papers presented at a homonym symposium held in Iasi in 2019, the book honors the memory of Alexandru Ioan Cuza and his actions which aided the development of the unified Romanian state.